2018
DOI: 10.3390/ijms19020436
|View full text |Cite
|
Sign up to set email alerts
|

When Immune Cells Turn Bad—Tumor-Associated Microglia/Macrophages in Glioma

Abstract: As a substantial part of the brain tumor microenvironment (TME), glioma-associated microglia/macrophages (GAMs) have an emerging role in tumor progression and in controlling anti-tumor immune responses. We review challenges and improvements of cell models and highlight the contribution of this highly plastic cell population to an immunosuppressive TME, besides their well-known functional role regarding glioma cell invasion and angiogenesis. Finally, we summarize first therapeutic interventions to target GAMs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
266
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(282 citation statements)
references
References 166 publications
3
266
1
1
Order By: Relevance
“…Glioma cells could release multiple cytokines that promote the infiltration of various immune cells such as MDSCs, microglia, Tregs, macrophages, CD8 T cells, and CD4 T cells into the tumor microenvironment, as tumors not only recruit immune cells, but also transform said cells into phenotypes that can help tumor cells evade immune system surveillance (Table ). For example, Roesch et al reported that macrophages/glioma‐associated microglia (GAMs) tend to gather in tumor sites and generate an immunosuppressive tumor microenvironment which promote glioma invasion, growth, and angiogenesis . Interestingly, one novel discovery of the present study is that COPB2 was involved in the immune microenvironment of glioma.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Glioma cells could release multiple cytokines that promote the infiltration of various immune cells such as MDSCs, microglia, Tregs, macrophages, CD8 T cells, and CD4 T cells into the tumor microenvironment, as tumors not only recruit immune cells, but also transform said cells into phenotypes that can help tumor cells evade immune system surveillance (Table ). For example, Roesch et al reported that macrophages/glioma‐associated microglia (GAMs) tend to gather in tumor sites and generate an immunosuppressive tumor microenvironment which promote glioma invasion, growth, and angiogenesis . Interestingly, one novel discovery of the present study is that COPB2 was involved in the immune microenvironment of glioma.…”
Section: Discussionmentioning
confidence: 56%
“…. For example, Roesch et al23 reported that macrophages/glioma-associated microglia (GAMs) tend to gather in tumor sites and generate an immunosuppressive tumor microenvironment which promote glioma invasion, growth, and angiogenesis 22,24. Interestingly, one novel discovery of the present study is that COPB2 was involved in the immune microenvironment of glioma.…”
mentioning
confidence: 99%
“…This hypothesis needs to be further validated in future work by assessing the recruitment of the host immune system elements through histopathological validation during TRI maximum and minimum values: in addition to CD3 and Iba‐1, other markers such as FoxP3 (regulatory T lymphocytes) or specific markers for different polarization extremes of macrophages (M1 and M2 subtypes) will be useful. Importantly, this may be of relevance due to the fact that macrophages/microglia intimately interact with tumour cells and may contribute, depending on the cellular subtype, to tumour growth, migration and invasion of tumour cell, destruction of the extracellular matrix, neoangiogenesis and an immunosuppressive microenvironment . Also, their quantification at different time points along therapy protocols would be of help to understand better their potential contribution to the metabolomics pattern of responding and non‐responding tumours.…”
Section: Discussionmentioning
confidence: 99%
“…GBs and other tumors have a mixture of M1 and M2‐like TAMs, and often these cells have elements of both phenotypes (Broekman et al, ). Typically, M2‐like TAMs accumulate in GB in response to secreted factors such as M‐CSF, thereby promoting immunosuppression and tumor progression (Roesch, Rapp, Dettling, & Herold‐Mende, ). M1‐like TAMs, however, are cytotoxic to tumors, so the shift we observed likely contributed to the attenuated tumor growth and prolonged survival in HuR KO mice (Chen & Hambardzumyan, ; Mantovani, Marchesi, Malesci, Laghi, & Allavena, ).…”
Section: Discussionmentioning
confidence: 99%
“…****p < .0001. All experiments were performed in triplicate and the data points are the mean ± SD of counted cells in at least 10 high-powered fields [Color figure can be viewed at wileyonlinelibrary.com] tumor progression(Roesch, Rapp, Dettling, & Herold-Mende, 2018).…”
mentioning
confidence: 99%